Comparisons of GnRH antagonist versus GnRH agonist protocol in supposed normal ovarian responders undergoing IVF: a systematic review and meta-analysis. - Jin-song Xiao (Public Library of Science (PLoS), 2014)
Objective To evaluate the effectiveness and safety of GnRH antagonist and GnRH agonist in supposed normal ovarian responders undergoing IVF. Methods Data from 6 databases were retrieved for this study. The RCTs of GnRH agonist and GnRH antagonist use during IVF-EF therapy for patients with supposed normal ovarian response were included. A meta-analysis was performed with Revman 5.1software. Results Twenty-three RCTs met the inclusion criteria. The number of stimulation days (mean difference (MD): -0.66, 95% confidence interval (CI): -1.04∼-0.27), Gn amount (MD: -2.92, 95% CI: -5.0∼-0.85), E2 values on the day of HCG (MD: -330.39, 95% CI: -510.51∼-150.26), Number of oocytes retrieved (MD: -1.33, 95% CI: -2.02∼-0.64), clinical pregnancy rate (odds ratio (OR): 0.87, 95% CI: 0.75-1.0), and ovarian hyperstimulation syndrome (OHSS) incidence (OR: 0.59, 95% CI: 0.42∼0.82) were significantly lower in GnRH antagonist protocol than GnRH agonist protocol. However, the endometrial thickness on the day of HCG (MD: -0.04, 95% CI: -0.23∼0.14), the ongoing pregnancy rate (OR: 0.87, 95% CI: 0.74∼1.03), live birth rate (OR: 0.89, 95% CI: 0.64∼1.24), miscarriage rate (OR: 1.17, 95% CI: 0.85∼1.61), and cycle cancellation rate (OR: 1.11, 95% CI: 0.90∼1.37) did not significantly differ between the 2 groups. Conclusions During IVF treatment for patients with supposed normal responses, the incidence of OHSS were significantly lower, whereas the ongoing pregnancy and live birth rates were similar in the GnRH antagonist compared with the standard long GnRH agonist protocols.